2020
DOI: 10.3390/ma13173742
|View full text |Cite
|
Sign up to set email alerts
|

High Thermally Stable and Melt Processable Polyimide Resins Based on Phenylethynyl-Terminated Oligoimides Containing Siloxane Structure

Abstract: A series of 4-phenylethnylphthalic anhydride (PEPA)-terminated oligoimides were prepared by co-oligomerizing isomeric dianhydrides, i.e., 2,3,3′,4′-biphenyltetracarboxylic dianhydride (a-BPDA), 2,3,3′,4′-benzophenonetetracarboxylic dianhydride (a-BTDA) or 2,3,3′,4′-diphenylethertetracarboxylic dianhydride (a-ODPA), with diamines mixture of bis(4-aminophenoxy)dimethyl silane (APDS) and 2,2′-bis(trifluoromethyl) benzidine (TFDB). The effects of siloxane content and dianhydride structure on the rheological proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…25,26 The 1625 cm À1 is the frequency-doubled absorption peak of the benzene ring. 27 It can be seen from the figure that with the increase of the amount of TFMB, its benzene ring frequency doubling absorption peak and C F absorption peak are more obvious, so it can be speculated that TFMB and MF have undergone a copolymerization reaction, but the NMR is still needed to further determine the MFF-TFMB molecular structure.…”
Section: Ftir Analysis Of Mff and Mff-tfmb Fibersmentioning
confidence: 99%
“…25,26 The 1625 cm À1 is the frequency-doubled absorption peak of the benzene ring. 27 It can be seen from the figure that with the increase of the amount of TFMB, its benzene ring frequency doubling absorption peak and C F absorption peak are more obvious, so it can be speculated that TFMB and MF have undergone a copolymerization reaction, but the NMR is still needed to further determine the MFF-TFMB molecular structure.…”
Section: Ftir Analysis Of Mff and Mff-tfmb Fibersmentioning
confidence: 99%
“…Phenylethynyl-terminated imide (PETI) oligomers and their derived polymer networks are broadly employed in high-temperature polymer composite applications in the aerospace industry. PETI-type oligomers undergo crosslinking through radical polymerization at elevated temperatures (325–400 °C), forming linear acetylenic structures at lower temperatures around 325 °C and crosslinked cyclized rings at temperatures greater than 350 °C. Recent studies have incorporated ortho-hydroxyl functionalities into the backbone of PETI imide oligomers, enabling TR during network formation. TR conversion and the resulting film properties such as dielectric constant, glass transition temperature ( T g ), and thermal degradation of the crosslinked TR-PBO networks (TR-PBOx) were elucidated, while their pore structures and properties remain less understood.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Carbon fiber composites based on organic resins with higher thermal stability have been available for a long time and have been used in a variety of electronics, energy, machinery, and aerospace applications. [2,3] Previous studies have reported on the development of a thermoset polyimide-based composite system, suitable for manufacturing by Resin Transfer Molding (RTM), with a glass transition temperature (T g ) between 340 and 466 C. [4][5][6] The effect of long-term exposures to high temperatures on the mechanical properties, as well as thermal cycling, have also been studied. [7,8] It was shown that during exposure to up to 320 C for 500 h in air, mostly the matrix and matrix-fiber interface properties were degraded.…”
Section: Introductionmentioning
confidence: 99%